Ultrasonic–microwave assisted extraction of total triterpenoid acids from Corni Fructus and hypoglycemic and hypolipidemic activities of the extract in mice. Issue 12 (23rd November 2020) - Han, Binkai; Niu, Dou; Wang, Ting; An, Shujing; Wang, Yanzhen; Chen, Xue; Bi, Huailong; Xue, Xiaochang; Kang, Jiefang
Abstract : Hypoglycemic and hypolipidemic activities and underlying mechanisms of total triterpenoid acids from Corni Fructus. Abstract : Triterpene acids, the main component of Corni Fructus, could improve diabetes mellitus, for which the underlying hypoglycemic mechanism is still unclear, in patients. In this study, total triterpenoid acids were extracted by ultrasonic–microwave assisted extraction optimized by the response surface methodology. The extract was then purified with an X-5 macroporous resin, and the yield of total triterpenoid acids increased to 281.24 mg g −1 as compared with the 35.71 mg g −1 obtained by unassisted extraction. The contents of five components were determined by ultrafast performance liquid chromatography. In addition, the hypoglycemic and hypolipidemic activities of total triterpenoid acids in diabetic mice induced by streptozotocin and a high fat diet were studied. The results indicated that all parameters (oral glucose tolerance, insulin resistance and liver damage) related to diabetes were significantly improved by total triterpenoid acids. Furthermore, total triterpenoid acids significantly recovered the expression level of AMP-activated protein kinase and its downstream proteins, including acetyl–CoA carboxylase, carnitine palmityltransferase-1, peroxisome proliferator-activated receptor alpha, sterol regulatory element-binding protein 1c and fatty acid synthase. Altogether, total triterpenoid acids could ameliorate hyperlipidemia and hyperglycemia in diabetic mice, probably by activating the AMP-activated protein kinase-peroxisome proliferator-activated receptor signaling pathway and inhibiting the sterol regulatory element-binding protein 1c and fatty acid synthase signaling pathways. Therefore, total triterpene acids, isolated from Corni Fructus which is a prevailing health food, could be a functional food ingredient with therapeutic and commercial values.